PENGARUH RASIO NPL (NON PERFORMING LOAN), GCG (GOOD CORPORATE GOVERMANCE), NIM (NET INTEREST MARGIN), CAR (CAPITAL ADEQUACY RATIO) DAN BOPO (BEBAN OPERASIONAL TERHADAP PENDAPATAN OPERASIONAL) TERHADAP HARGA SAHAM DENGAN ROE (RETURN ON EQUITY) SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA 2008-2013 - Hairunnisah, Ade Isyana (MEASUREMENT, 2015)
This research aim  to know influence of  variable Non Performing Loan (NPL), Good Corporate Governance (GCG), Net Interest Margin (NIM), Capital Adequacy Ratio (CAR) and Operating Cost to Operating Revenue (BOPO) to share Price with  Return on Equity  (ROE) as a moderating at the banking emiten of listed in Indoesia Stock Exchange.The sample taken from 20 (twenty) banking emiten listing in Indonesia Stock Exchange by the 32 (thirty two) population of Banking Emiten in Indonesia Stock Exchange. Sample taking with purposive method sampling with period of research between of 2008 up to year of 2013. Analisys method the used is moderating regression Analisy with SPSS ( Statistical Product and Service Solutions).The research results  partial show Non Performing Loan (NPL), Good Corporate Governance (GCG),  Operating Cost to Operating Revenue (BOPO) and Return on Equity  (ROE)  is significance effect  to Share Price  While Net Interest Margin (NIM) and Capital Adequacy Ratio (CAR) not significance effect to Share Price by market Value. Thereby role of  Return on Equity  (ROE)  only as moderating variabel strengthan of causality of  Non Performing Loan (NPL), Good Corporate Governance (GCG), and  Operating Cost to Operating Revenue (BOPO) to Share Price by market Value.